Utility of FNAC in the Clinicopathologic Evaluation of Benign Thyroid Lesions - babu, P. venkataramana; Neeraja, M.; jyothi bai, Sarella; Varalakshmi, K.P.; Bhavani, C.; naik, V. Sivasankara (International Journal of Medical Research and Review, 2015)
Background: Thyroid swellings are common clinical presentations in the male and females, majority of them are benign in nature and do not require surgery. Fine needle aspiration cytology in the diagnosis of thyroid lesions is an easy and cost-effective method. Aim of this study was to assess the effectiveness of FNAC in the evaluation of benign thyroid lesions by clinical, histopathologic analysis and compare the consistency of the results with the literature. Materials and Methods: Over a period of 3 years prospective study done from January 2001 to December 2003 in the cytopathology department, Sri Venkateswara Medical College, Tirupati, Andhra Pradesh. Two hundred and fifty (250) cases of palpable and clinically benign thyroid lesions were analyzed by fine needle aspiration, preceded by thorough clinical evaluation. Out of these 250 cases only 65 patients under went surgical excision and these were available for histopathological correlation. Staining techniques used are Haematoxylin and Eosin and May-Grun Wald Giemsa stain. Results: out of 250 cases, 65 were available for histopathological correlation. Among which 10 had malignant, which were excluded from the present study. Out of 55 benign thyroid lesions 20(36.3%) cases were Multinodular goiter, 17(30.9%) were Follicular adenoma, 10(18.1%) were Hashimoto’s thyroiditis. Sensitivity, specificity, positive predictive value, negative predictive values were 90,100,100 & 98.21 % respectively. Finally accuracy rate was 98.46%. Conclusion: Fine needle aspiration cytology is a simple, cost effective, rapid to perform procedure with high degree of accuracy and is recommended as first line investigation for the diagnosis of thyroid lesions.